GAMBARAN PELAKSANAAN PENCEGAHAN PLEBITIS DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM DAERAH KABUPATEN CIAMIS TAHUN 2019 - wulan ayu rahmawati; heni marliany; ima sukmawati (LPPM STIKes Muhammadiyah Ciamis, 2020)
Plebitis is a nosocomial infection originating from microorganisms experienced by patients obtained during the patient's hospitalization. The high incidence of nosocomial infections due to infusion in the form ofplebitis may be due to the non-implementation of intravenous installation by nurses in accordance with the standard operational procedures for infusion set by each hospital. SOP for infusion in all hospitals in Indonesia to prevent nosocomia infection. The research method is descriptive with a quantitative approach. The population in this study were all nurses and midwives who worked in the Inpatient Installation Room of the Ciamis District General Hospital as many as 327 people. Sampling in thisstudy used a quota sampling technique to obtain a sample of 77 people. The results showed that the prevention ofplebitis in Inpatient Installation of Ciamis District General Hospital in 2019, from 77 respondents, it can be concluded that most of the good categories were 48 people (62.3%) and a small number were less than 13 people (16,9%). The implementation of prevention of plebitis in theInpatient Installation of the General Hospital of the Ciamis Regency in 2019 was mostly categorized as good